If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(2x + 5) + ln(x + -7) + -2lnx = 0 Reorder the terms: ln(5 + 2x) + ln(x + -7) + -2lnx = 0 (5 * ln + 2x * ln) + ln(x + -7) + -2lnx = 0 (5ln + 2lnx) + ln(x + -7) + -2lnx = 0 Reorder the terms: 5ln + 2lnx + ln(-7 + x) + -2lnx = 0 5ln + 2lnx + (-7 * ln + x * ln) + -2lnx = 0 5ln + 2lnx + (-7ln + lnx) + -2lnx = 0 Reorder the terms: 5ln + -7ln + 2lnx + lnx + -2lnx = 0 Combine like terms: 5ln + -7ln = -2ln -2ln + 2lnx + lnx + -2lnx = 0 Combine like terms: 2lnx + lnx = 3lnx -2ln + 3lnx + -2lnx = 0 Combine like terms: 3lnx + -2lnx = 1lnx -2ln + 1lnx = 0 Solving -2ln + 1lnx = 0 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'ln'. ln(-2 + x) = 0Subproblem 1
Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-2 + x)' equal to zero and attempt to solve: Simplifying -2 + x = 0 Solving -2 + x = 0 Move all terms containing l to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + x = 0 + 2 x = 0 + 2 Combine like terms: 0 + 2 = 2 x = 2 Add '-1x' to each side of the equation. x + -1x = 2 + -1x Combine like terms: x + -1x = 0 0 = 2 + -1x Simplifying 0 = 2 + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 9x-5x=4 | | 4r-15=21 | | 8x+5y=-77 | | 20-2w=12 | | 8K-3K=25 | | 4+3n=8n-3(n-4) | | -4-2m-m=-3 | | 10x+4=8x-(2-3x) | | (9x-8)-(x+4)=0 | | (9x+5)-(4x+3)=0 | | 5(z+2)=10z | | 4b+11=75 | | 3y-9=13+y | | a(x+c)+b(x+d)-ax=e | | 8a-3=5(a+7)+3z | | 3(2-x)=3x | | 6000-2000x=2000-1000x | | 19=20-7d-d | | ax+b+a(x+d)=b | | 7n^2=48n | | -5+3x=4x-3 | | 3x-(x+n)=m | | 2x+x+7=8.5 | | 12+1=-3y+7y+13 | | lnx-6[ln(x-2)+ln(x+2)]=x | | -15(k+1)=-4 | | u-7=6 | | 6(4+s)=38 | | 6000-2000x=2000-1000 | | 8x-16x=-12-126-6 | | 2g-15=3 | | 3(x-3)2+-2=26 |